The Pengaruh ransum yang mengandung biji durian (Durio zibethinus Murr.) terhadap fermentabilitas dan kecernaan secara in vitro - Iman Hernaman; Esatya Mahardika; Angga Purnawisda; Ana R. Tarmidi (Jurnal Ilmu Peternakan Terapan, 2022)
The aims of this study to examine the use of durian seed flour in rations on fermentability and digestibility in beef cattle fattening rations. The study was conducted experimentally with 5 treatments of durian flour: 0, 8, 16, 24, and 32% and each treatment carried out 4 replications. In vitro technique was used to evaluate the fermentability and digestibility of the diet. The data were analyzed by the ANOVA test, the relationship between treatment and variables was analyzed by regression and correlation, while the relationship between variables was tested by Pearson Product Moment Correlation. The results showed that the higher the use of durian seeds decreased the lower (P<0.05) the content of volatile fatty acids (ALT), ammonia, dry matter digestibility (KCBK), and organic matter digestibility (KCBO). This pattern is indicated by a negative linear regression with a very strong correlation level (r) >80. Although there was a decrease, the use of durian seed flour at a level of 16% produced ALT, ammonia, KCBK, and KCBO respectively 141.38 mM, 3.74 mM, 60.46%, and 68.28%. The results showed that there was a relationship between KCBK and KCBO on ALT and ammonia which was very significant (P<0.01) and very strong (r>0.80), so it can be concluded that the use of 16% durian seeds gave the best results. Durian seeds have the potential to be used as a mixture of cow feed.